Malta and Tunisia, shared stories and common heritage - Taboubi, Abdellatif (Times of Malta, 2021)
If we go back in time, the ancient authors say that a king of Malta called Battus was on good terms with Queen Elyssa of Carthage. When she died by throwing herself into a blaze, her sister, Anna found refuge in Malta, sheltered by this king. St Joseph church in Houmt el-Souk, in Djerba. In...
Keywords: Christianisme – Djerba; Emigration – Malte – Djerba; Relations – Djerba – Malte